Design and Development of a Rice Mill Booking Application in Langowan - Mandias, Green Ferry; Tangka, George; Maleke, Naftali Christian; Ambat, Bravi (12th International Scholars Conference 2025, 2026)
Agriculture serves as one of the backbone sectors of Indonesia’s economy, providing essential food supplies for a significant portion of the population. Langowan, situated in North Sulawesi, possesses its own distinctive characteristics in contributing to the agricultural sector within the region. Rice milling plays a crucial role in processing farmers' harvests into consumable rice. In the current era of information technology and mobile computing, leveraging mobile application technology based on the Android platform can offer an effective solution to address existing challenges. Mobile applications can facilitate access and interaction between farmers and rice mill operators, making the ordering process more transparent, fast, and efficient. However, in rice milling locations in the Langowan area, it is observed that there is a scheduling uncertainty due to a lack of clear information regarding milling schedules, thus posing difficulties for farmers. Therefore, there is a need to design an Android-based mobile application to facilitate the rice milling ordering process effectively online. This research adopts the Prototyping model method and utilizes software such as React Native, Figma, and Firebase. The result is a designed and developed application that can assist in online rice milling ordering in the Langowan District, and the application's functionality operates effectively.